Atrial Fibrillation in a Patient with Interatrial Block after Successful Atrial Flutter Ablation: May Interatrial Block Be a Link for a Continuum of Atrial Arrhythmias? - Antonopoulos, MD, PhD, FESC, Athanassios; Donigaglia, MD, Daniele; Amadei, MD, Gian Andrea (International Journal of Innovative Research in Medical Science, 2022)
Background: Electrocardiographic interatrial block (IAB) typically exists when a conduction delay over the Bachmann’s bundle is present. By analogy to other types of block, there is a continuum of IAB severity; partial IAB is defined as a P-wave duration 120 ms and advanced interatrial block (aIAB) is defined as a P-wave duration 120 ms in conjunction with biphasic P-wave morphology in inferior leads II, III, and aVF. Moreover, IAB seems to be a key factor in the genesis of atrial fibrillation (AF). On the contrary, it is not clear if the presence of advanced IAB may be associated with an occurrence of AF after cavotricuspid atrial flutter ablation in patients without previous episodes of atrial fibrillation. So, may be useful to evaluate on surface electrocardiogram the P-wave morphology and duration in sinus rhythm after the ablation procedure just to identify patients at high risk for atrial fibrillation development. Advanced IAB is frequently associated with atrial tachyarrhythmias, and it was found to predict AF and may be helpful for clinical decisions. Case presentation: In this case involving a man who underwent a typical atrial flutter ablation, we documented that aIAB during the post-ablation period which seems to induce atial fibrillation episodes. To our knowledge, it is unusual to detect an aIAB after cavotricuspid atrial flutter ablation and subsequently associate it with a new onset of AF. Conclusions: Our observation supports a possible aIAB induction of AF after cavotricuspid atrial flutter ablation and potentially may representing a link in the continuum of atrial arrhythmias. P-wave morphology and duration should be better evaluated soon after AFlu ablation to better stratify patients who are at high risk for atrial fibrillation development and eventually prolonged anti-coagulation therapy.